Comparison of the quick SOFA score with glasgow-blatchford and rockall scores in predicting severity in patients with upper gastrointestinal bleeding - Taşlıdere, Bahadır; Sönmez, Ertan; Özcan, Ayşe Büşra; Mehmetaj, Liljana; Biberci Keskin, Elmas; Gülen, Bedia (W.B. Saunders, 2021)
Introduction: Upper gastrointestinal bleeding is one of the common causes of mortality and morbidity. The Rockall score (RS) and Glasgow-Blatchford score (GBS) are frequently used in determining the prognosis and predicting in-hospital adverse events, such as mortality, re-bleeding, hospital stay, and blood transfusion requirements. The quick Sepsis Related Organ Failure Assessment (qSOFA) score is easy and swift to calculate. The commonly used scores and the qSOFA score were compared and why and when these scores are most useful was investigated. Method: 133 patients admitted to the emergency department with upper gastrointestinal bleeding over the period of a year, were evaluated in this retrospective study. The RS, GBS and qSOFA score were calculated for each patient, and their relationship with in-hospital adverse events, such as length of hospitalization, rebleeding, endoscopic treatment, blood transfusion requirements, and mortality, was investigated. Results: The mean overall GBS was 9.72 ± 3.72 (0–19), while that of patients who did not survive was 14.0 ± 1.1 (13–16), with an area under the curve (AUC) of 0.901, a cutoff value of 12.5, and specificity (Spe) and sensitivity (Sen) of 1 and 0.82, respectively. The median value of the GBS, in terms of transfusion need, was 7.12 ± 4.01 (0–15). (AUC = 0.752, cut-off = 9.5, Spe = 0.79, Sen = 0.69). The median value of the qSOFA score, in terms of intensive care need, was 1.73 ± 0.7 (0–3) (AUC = 0.921, cut-off = 0.5, Spe = 0.93, Sen = 0.79). The RS median, in terms of re-bleeding, was 8.22 ± 0.97 (6–9). Conclusion: Early use of risk stratification scores in upper gastrointestinal bleeding is important due to the high risk of morbidity and mortality. All scoring systems were effective in predicting mortality, the need for intensive care, and re-bleeding. The GBS had a greater predictive power in terms of mortality and transfusion need, the qSOFA score for intensive care need, and the RS for re-bleeding. The simpler, more efficient, and more easily calculated qSOFA score can be used to estimate the severity of patients with upper gastrointestinal bleeding.
Keywords: Risk Scores; Upper Gastrointestinal System Bleeding; qSOFA Score; Adverse Event; Rockall Score; Glasgow-Blatchford Score